The nature of life and death : every body leaves a trace - Wiltshire, Patricia E. J (G.P. Putnam's Sons, 2019)
From mud tracks on a quiet country road to dirt specks on the soles of walking boots, forensic ecologist Patricia Wiltshire uses her decades of scientific expertise to find often-overlooked clues left behind by criminal activity. She detects evidence and eliminates hypotheses armed with little more than a microscope, eventually developing a compelling thesis of the who, what, how, and when of a crime. Wiltshire's remarkable accuracy has made her one of the most in-demand police consultants in the world, and her curiosity, humility, and passion for the truth have guided her every step of the way. A riveting blend of science writing and true-crime narrative, The Nature of Life and Death details Wiltshire's unique journey from college professor to crime fighter: solving murders, locating corpses, and exonerating the falsely accused. Along the way, she introduces us to the unseen world all around us and underneath our feet: plants, animals, pollen, spores, fungi, and microbes that we move through every day. Her story is a testament to the power of persistence and reveals how our relationship with the vast natural world reaches far deeper than we might think.